Role of Haematological Score in Early and Rapid Diagnosis of Neonatal Septicaemia - Khan, Shareen; Baki, MA; Halder, Amrita Lal; Haque, Afroza; Begum, Tahmina; Nahar, Nazmun (BIRDEM Medical Journal, 2017)
Background: Septicaemia is well documented as being one of the major causes of neonatal mortality and morbidity worldwide including Bangladesh. A haematological scoring system which includes total WBC count, absolute neutrophil count, platelet count and C reactive protein may be beneficial for the early and rapid diagnosis of neonatal septicaemia. So this study was done to see the role of the haematological score in neonatal septicaemia. Methods: This observational study was done in SCABU, BIRDEM General Hospital 2 from April 2012 to September 2012. One twenty neonates who were clinically suspected of septicaemia were enrolled in this study. A score of 1 was given for each of the haematological parameters. Blood culture was done in all neonates along with haematological score to prove septicaemia. Results: In this study 42 neonates had a score of 1,a score of 2 was present in 45 neonates. Score 3 was present in 23 neonates and score 4 was present in 10 patients. Among the 42 neonates having a score of 1, culture was negative in 69% and 30% had positive culture reports. In neonates with score 2, it was seen that almost half (46.4%) had a positive blood culture and the rest (53.3%) were culture negative. Twenty three neonates had a score of 3 among which 73.9 % were proven sepsis by positive culture reports. Blood culture was positive in 100 % patients with a score of 4. Conclusion: The higher the score the greater the chance of neonatal septicaemia. The haematological scoring system may aid the clinicians to use proper antibiotics at the right time and thus reduce neonatal morbidity and mortality. Birdem Med J 2017; 7(3): 212-215